Pengaruh Covid-19 Terhadap Usaha Mikro Kecil dan Menengah (UMKM) di Kawasan Ekonomi Khusus (KEK) Mandalika - Inka Nusamuda Pratama; Darmansyah Darmansyah; Ayatullah Hadi; Yudhi Lestanata; Hidayatullah Hidayatullah (Jurnal Ranah Publik Indonesia Kontemporer (Rapik), 2022)
The location of this research is in the Kuta MandalikaSpecial Economic Zone, Central Lombok Regency. The purpose of this study is to analyze the impact of Covid-19on the economy of Micro, Small and Medium Enterprises in the Kuta Mandalika Special Economic Zone, Central Lombok Regency. This research was conducted during the Covid-19pandemicin the period from December to January 2021. The existence of Covid-19actually has an impact on the economy of Micro, Small and Medium Enterprises, so it is the author's interest to research this problem. The population of this research is Micro, Small, and Medium Enterprises in the Kuta Mandalika Special Economic Zone. This study uses quantitative methods, where the number of respondents in this study were 100 who were taken by the slovhin formula. To analyze the data, this research uses simple linear regression analysis to see whether there is an impact of Covid-19on the economy of Micro, Small, and Medium Enterprises in the Kuta Mandalika Special Economic Zone, Central Lombok Regency. The results showed that Covid-19had an impact on the economy of Micro, Small and Medium Enterprises in the Kuta Mandalika Special Economic Zone, where the magnitude of the effect was 7.84%. From the results of calculations and previous discussions based on the results of a simple linear regression test, it can be concluded that the Covid-19variable has an impact on the variables of Micro, Small and Medium Enterprises. Where every increase of one Covid-19unit will hamper the economy of Micro, Small and Medium Enterprises in the Kuta Mandalika Special Economic Zone, Central Lombok Regency.